RLC passive damped LCL single-phase voltage source inverter with capability to operate in grid-connected and islanded modes: design and control strategy - Ugaz Pena, Jose Carlos (2020)
A design procedure for an RLC damping branch applied at a voltage source inverter followed by an LCL output filter is carried out in this paper. The main purpose of the proposed methodology is to allow the system to operate properly in both grid-connected (GC) and islanded (IS) modes with smooth transitions between them. The usage of passive damping methods to smooth the resonating filters effects is well known. However, the design procedure of the damping branch is specific for either the GC or IS mode, and usually, the parameters tuned for an operation mode are unsuitable for the other one. Thereby, this paper contributes to presenting a methodology design of an RLC branch aimed to achieve damping effect for both operation modes, thus allowing the continuous operation with no hazardous transients during transitions. By means of the proposed approach, the passive elements are adequately designed in order to provide easy controller synthesis. Therefore, a two-loop control strategy is adopted where the inner loop controls the capacitor voltage and ensures the system stability for both operation modes; meanwhile, an additional outer loop controls the grid current for GC mode allowing active and reactive power flows. Experimental results for a 2-kW prototype are presented in order to validate the proposed design methodology and control strategy.